Serologic evidence of west nile virus infection in birds, Tamaulipas State, México - Fernández Salas, Ildefonso; Contreras Cordero, Juan Francisco; Blitvich, Bradley J.; González Rojas, José Ignacio; Cavazos Álvares, Amanda; Marlenee, Nicole L.; Elizondo Quiroga, Armando Erick; Loroño Pino, María Alba; Gubler, Duane J.; Calisher, Charles; Beaty, Barry J. (Vector borne and zoonotic diseases, 2003)
Following the introduction of West Nile virus (WNV) into North America in 1999, surveillance for WNV in migratory and resident birds was established in Tamaulipas State, northern México in December 2001. Overall, 796 birds representing 70 species and 10 orders were captured and assayed for antibodies to WNV. Nine birds had flavivirus-specific antibodies by epitope-blocking enzyme-linked immunosorbent assay; four were confirmed to have antibody to WNV by plaque reduction neutralization test. The WNV-infected birds were a house wren, mourning dove, verdin and Bewick's wren. The house wren is a migratory species; the other WNV-infected birds are presumably residents. The WNV-infected birds were all captured in March 2003. These data provide the first indirect evidence of WNV transmission among birds in northern México.